2007
DOI: 10.3174/ajnr.a0607
|View full text |Cite
|
Sign up to set email alerts
|

Distal Aneurysms of Cerebellar Arteries: Incidence, Clinical Presentation, and Outcome of Endovascular Parent Vessel Occlusion

Abstract: BACKGROUND AND PURPOSE:The aim of this retrospective study was to report the incidence, clinical presentation, and midterm clinical and imaging results of endovascular parent vessel occlusion of 11 patients with 13 distal cerebellar artery aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
72
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 15 publications
1
72
0
1
Order By: Relevance
“…The former can be treated by clip ligation at the neck, and the latter may be trapped or occluded surgically or endovascularly. 6,21,24,25,[29][30][31] The etiology of the AICA aneurysm is controversial: hemodynamic stress, embryonic vulnerability, flow-related vascular pathology, and arterial dissection by local trauma or nonspecific inflammation. 29,[32][33][34][35][36][37][38][39] Our study showed that 2 aneurysms were accompanied by AVMs and Moyamoya disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The former can be treated by clip ligation at the neck, and the latter may be trapped or occluded surgically or endovascularly. 6,21,24,25,[29][30][31] The etiology of the AICA aneurysm is controversial: hemodynamic stress, embryonic vulnerability, flow-related vascular pathology, and arterial dissection by local trauma or nonspecific inflammation. 29,[32][33][34][35][36][37][38][39] Our study showed that 2 aneurysms were accompanied by AVMs and Moyamoya disease.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been reported only 17 AICA aneurysms treated by EVT, all of which were in the distal AICA and were treated by parent artery occlusion, except in 2 cases. [22][23][24][25]29,30,[40][41][42][43][44][45][46][47] The reasons for EVT in proximal AICA aneurysms may be as follows: 1) development of technologies regarding endovascular devices, 2) all treated aneurysms not fusiform but saccular, and 3) accessibility to anatomic configuration by an endovascular device. Because all the treated AICA aneurysms were saccular, it was possible to preserve the parent artery with endosaccular embolization, and stent-assisted coiling was also applied in cases of the wideneck AICA aneurysms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,35 AICA aneurysms generally occur at the origin of this vessel at the basilar artery, but they can also occur distally at the CPA. 50 Treating these distal AICA aneurysms is challenging and generally complicated by a new-onset neurological deficit that is likely secondary to ischemia in the brainstem, middle cerebellar peduncle, or CNs. Sarkar and Link 58 reported a case of distal AICA aneurysm clipping with postsurgical increase in nystagmus and ataxia and findings on MRI of middle cerebellar peduncle stroke.…”
Section: Arterial Aneurysmsmentioning
confidence: 99%